Pengembangan HRIS Berbasis Web Menggunakan HTML Dan Laravel Di RKP Manajemen - Muhammad Abdillah; Fitri Bidayatul Hidayah; Abdul Rizal Kholiq; Wasis Haryono (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Efficient human resource (HR) management is the key to organizational success. However, manual processes that are still widely applied are often a source of inefficiency and data inaccuracy. This research aims to describe the process of developing a web-based Human Resource Information System (HRIS) at RKP Management. This system is designed to solve HR administration problems through integrated digital solutions. The development of this system uses the Laravel framework as a backend foundation and HTML/CSS/JavaScript for user interface design. The development method used is a structured waterfall model. The main features designed include employee data management, innovative attendance based on face detection and location validation, management of tardiness and leave quotas, and a centralized reporting dashboard for the CEO. Although the system is still under development, a prototype interface has been created to visualize the expected functionality. The system design is expected to provide a solid framework for full implementation, which will ultimately improve data accuracy, operational efficiency, and support strategic decision-making at RKP Management.